2017
DOI: 10.5944/etfvi.10.2017.18748
|View full text |Cite
|
Sign up to set email alerts
|

El Proyecto School on the Cloud: Lecciones Aprendidas = School on the Cloud Project: Lessons Learned

Abstract: ResumenSchool on the Cloud es un Proyecto europeo Acción Clave 3 del programa de Aprendizaje Permanente de la UE. En sus tres años de andadura ha evidenciado la potencialidad del empleo de la nube para el aprendizaje en todos los niveles educativos con la finalidad de llamar la atención a los agentes responsables de la educación en Europa sobre ello. Diversas actividades y resultados de investigación han permitido llegar a esa conclusión, para cuya consecución se proponen algunas medidas concretas, como por ej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Obtaining data from the SDIs and integrating them into the Geographic Information Systems on the cloud or WebGIS is of great assistance for these objectives in education [13][14][15][16][17][18], because it is an excellent field for the active teaching of the use of collaborative working techniques, and it also leads to the benefits that the TPACK promotes. It has been shown that a WebGIS reinforces learning and is integrated into a novel educational current whose success in the classroom has been noted by numerous authors [19][20][21][22][23][24][25][26][27].…”
Section: The Wealth Of Data Of the Spatial Data Infrastructures For Addressing The Sustainable Development Goalsmentioning
confidence: 99%
“…Obtaining data from the SDIs and integrating them into the Geographic Information Systems on the cloud or WebGIS is of great assistance for these objectives in education [13][14][15][16][17][18], because it is an excellent field for the active teaching of the use of collaborative working techniques, and it also leads to the benefits that the TPACK promotes. It has been shown that a WebGIS reinforces learning and is integrated into a novel educational current whose success in the classroom has been noted by numerous authors [19][20][21][22][23][24][25][26][27].…”
Section: The Wealth Of Data Of the Spatial Data Infrastructures For Addressing The Sustainable Development Goalsmentioning
confidence: 99%